2017
DOI: 10.1139/cjss-2016-0119
|View full text |Cite
|
Sign up to set email alerts
|

Do volatile solids from bedding materials increase greenhouse gas emissions for stored dairy manure?

Abstract: Current approaches for estimating greenhouse gas (GHG) emissions from manure storages do not consider contributions due to bedding materials. Compared with sand, wood-based bedding has the potential to increase volatile solids and total solids concentrations and favour crust formation in liquid dairy manure. In this study, the GHG emissions from wood and sand bedding slurries were evaluated monitored continuously for 207 d (1 May-24 Nov. 2014) under "warm season" storage conditions. For both slurries, methane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
(56 reference statements)
3
13
2
Order By: Relevance
“…Control and medium pH treatments had 96 and 97% CH 4 reductions. This is consistent with Le Riche et al (2016, 2017), who reported that 98% of CO 2 –eq emissions were from CH 4 for manure from the same farm. The remainder of the total emissions in the control and medium pH treatments were from direct and indirect N 2 O emissions, which were <4% of the total CO 2 –eq.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Control and medium pH treatments had 96 and 97% CH 4 reductions. This is consistent with Le Riche et al (2016, 2017), who reported that 98% of CO 2 –eq emissions were from CH 4 for manure from the same farm. The remainder of the total emissions in the control and medium pH treatments were from direct and indirect N 2 O emissions, which were <4% of the total CO 2 –eq.…”
Section: Resultssupporting
confidence: 92%
“…There was limited manure surface crusting observed in all tanks, which has previously been observed for sand bedding manure (Le Riche et al, 2017). The limited crusting suggests that there were few low‐density solids that floated to the top and the majority settled to the bottom.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations